Clinical Outcomes of Use of Low Vision Aids for Enhancement of Residual Vision in Diabetic Retinopathy: Doi: 10.36351/pjo.v37i1.1138 - Shah, Mufarriq; Khan, Muhammad Tariq (Pakistan Journal of Ophthalmology, 2020)
Purpose: To investigate clinical outcomes of use of low vision aids for enhancement of residual vision in people with Diabetic Retinopathy (DR). Study Design: Cross-sectional study. Place and Duration of Study: Hayatabad Medical Complex Peshawar, from January 2018 to December 2019. Methods: Eighty-one consecutive patients with DR were assessed in a low vision clinic for vision rehabilitation. Data regarding distance and near visual acuity (VA), refractive error, types of low vision aids (LVAs), VA with best correction and with LVAs were collected and analyzed. Results: A total of 81 people with DR, 63% were male. Mean age was 58.48 ± 13.54 years. With mean duration of 12.6 years of diabetes, 29.6% had Insulin dependent while 70.4% had non-Insulin dependent diabetes. At presentation, 63% had moderate vision impairment (0.5 > VA > 1.0), 14.8% had severe vision impairment (1.0 > VA > 1.3) and 22.2% had blindness (VA < 1.3).With LVAs, 97.5% achieved distance VA of Log MAR 0.4 or better. Mean improvement in distance VA with LVAs was Log MAR 0.95 ± 0.19 (P = 0.000; 95% CI). Near VA improved significantly with LVAs and the number of participants who could see 1M or better with their own glasses increased from 7.4% to 97.5% (p < 0.001). Binocular telescopes 2.1X were the most preferred low vision device for distance vision and prismatic magnifying spectacles for near vision. Conclusion: Visual rehabilitation through the use of LVAs was helpful in patients with low vision caused by diabetic retinopathy. Hence, improving the quality of life. Key Words: Diabetic retinopathy, blindness, visual rehabilitation, low vision aids, Pakistan.